The extreme environments of elite sports - Poimann, Dino; Eckhardt, Holger; Cibis, Tobias; Wirth, Markus (Engineering and Medicine in Extreme Environments, 2022)
This chapter discusses the main characteristics and challenges of the elite sports environment, derived impacts on the athlete's body and mind, as well as implications of the training process. "Elite Sports" is a common but not well-defined phrase. In this chapter, we refer to the elite sports environment as "the top competitions in a sport (e.g., world championships/series, Olympic Games, etc.) and the training process with the purpose to compete/succeed in competition. " Main characteristics are the search for optimal, on point performance through constantly improving fitness for a specific context of top competition. This implies a high investment of energy and time over a long period. Elite sports competes globally and is in the focus of public attention. Therefore, elite sports is not just extreme in terms of extraordinary physical and mental demands imposed by the movement task but also in respect to the special social and more or less superficial environment in which it takes place. The main challenge of elite sports is to handle physical, psychological, and social stress in the right way. Utilizing it as the motor for the human adaptation capacity in the training process and promoter of optimal performance. High loads of biopsychological stress are needed to optimize fitness. The meaning of the concepts of resilience and antifragility is discussed. Foremost, it is important to balance the stress with sufficient recovery, as well as coping with and minimizing stressors, which are counteracting the adaptive process.
CRIS-Team Scopus Importer:2024-12-16